2017
DOI: 10.4174/astr.2017.93.5.246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of end-to-side inverted mattress pancreaticojejunostomy following central pancreatectomy on the prevention of pancreatic fistula

Abstract: PurposeCentral pancreatectomy (CP) may be indicated for the treatment of benign or low-grade malignant tumor in the neck and proximal body of the pancreas. Pancreatic fistula is one of the most common complications after CP. In this study, we suggested an inverted mattress pancreaticojejunostomy (IM-PJ) technique to decrease the risk of pancreatic fistula.MethodsBetween 2010 and 2015, CP was performed with IM-PJ for 10 consecutive patients with a benign or low-grade malignant tumor in the neck and proximal bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…As previously published, our data showed that IM-PJ reduced the risk of Grade C POPF and serious complications such as a gastroduodenal artery pseudoaneurysm after pancreaticoduodenectmy [ 4 ]. No pancreatic fistula occurred from IM-PJ after a central pancreatectomy [ 5 ]. Based on our experiences of reporting the safety of IM-PJ for a pancreaticoduodenectmy and central pancreatectomy, we decided to apply the same technique for this patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously published, our data showed that IM-PJ reduced the risk of Grade C POPF and serious complications such as a gastroduodenal artery pseudoaneurysm after pancreaticoduodenectmy [ 4 ]. No pancreatic fistula occurred from IM-PJ after a central pancreatectomy [ 5 ]. Based on our experiences of reporting the safety of IM-PJ for a pancreaticoduodenectmy and central pancreatectomy, we decided to apply the same technique for this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the conventional “duct to mucosa” technique after a pancreaticoduodenectmy, the IM-PJ, effectively reduced the risk of grade C POPF and serious complications such as a gastroduodenal artery pseudoaneurysm [ 4 ]. Similarly, no pancreatic fistula occurred from IM-PJ after a central pancreatectomy [ 5 ]. Based on the previous reports of low morbidity following IM-PJ, we decided to apply this technique after a distal pancreatectomy for a patient with chronic pancreatitis with proximal pancreatic duct obstruction, caused by an impacted stone, requiring the Duval procedure.…”
Section: Introductionmentioning
confidence: 99%
“…However, postoperative morbidity after PD remains high with the pancreato-enteric anastomosis being a major source of complications accounts for about 5% to 30% of the cases (5,6,7). Various modifications of the pancreatico jejuna anastomosis like binding pancreaticojejunostomy, inverted mattress pancreaticojejunostomy, papillary-like pancreaticojejunostomy have shown a benefit, yet none has become the standard and foolproof method in reducing the incidence of POPF (8,9,10). Therefore this short paper describes the transcription of a new technique used in Manchester, the UK which is an end to side, duct to mucosa pancreaticojejunostomy with an insertion of a transanastomotic silicone stent.…”
Section: Introductionmentioning
confidence: 99%